2012
DOI: 10.1111/j.1467-789x.2012.01016.x
|View full text |Cite
|
Sign up to set email alerts
|

The expanding burden of cardiometabolic risk in China: the China Health and Nutrition Survey

Abstract: Background China faces a major increase in cardiovascular disease, yet there is limited population-based data on risk factors, particularly in children. Methods and Results Fasting blood samples, anthropometry and blood pressure were collected on 9,244 children and adults aged ≥7 years in late 2009 as part of the national China Health and Nutrition Survey. Prevalent overweight, elevated blood pressure, and cardiometabolic risk factors: glucose, HbA1c, triglycerides (TG), total cholesterol (TC), high and low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
210
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(219 citation statements)
references
References 36 publications
(36 reference statements)
6
210
0
2
Order By: Relevance
“…Physical activity was identified into two categories (yes/no), with the question 'Do you participate in this activity (includes: martial arts, gymnastics, dancing, acrobatics, running, swimming, soccer, basketball, tennis, badminton, volleyball and others)?' Urbanicity was defined by a multidimensional twelve-component urbanization index, which has been explained in previous studies (30,31) . Tertiles of the urbanization index were used to define low, medium and high urbanicity for the present study.…”
Section: Other Variablesmentioning
confidence: 99%
“…Physical activity was identified into two categories (yes/no), with the question 'Do you participate in this activity (includes: martial arts, gymnastics, dancing, acrobatics, running, swimming, soccer, basketball, tennis, badminton, volleyball and others)?' Urbanicity was defined by a multidimensional twelve-component urbanization index, which has been explained in previous studies (30,31) . Tertiles of the urbanization index were used to define low, medium and high urbanicity for the present study.…”
Section: Other Variablesmentioning
confidence: 99%
“…The authors speculated that the observed increase in CVD risk observed in South Asian countries could be attributed to the effects of increasing urbanization on CVD risk factors [5]. The nutritional consequences of migrating from a low-income country to the US are similar to the nutritional consequences of migrating from a rural lifestyle to an urban lifestyle and similar to the effects of ''modernization'' in developing countries [19][20][21]. These consequences include increases reported for various nutrition-related CVD risk factors, including increased intake of saturated fats (i.e., animal foods), refined carbohydrates, sodium and decreased intake of dietary fiber and potassium [5].…”
Section: Introductionmentioning
confidence: 99%
“…To shed light on the association between long work hours and cardiometabolic risks in general (diabetes, dyslipidaemia, hypertension, and inflammation), we analyze biomarker data from the CHNS, which, however, are only available for 2009 and for quite a small sample. Specifically, we create binary variables for prediabetes, diabetes, dyslipidaemia, and inflammation, and then, following Yan et al (2012) and Ning and Bloomgarden (2013), define the prediabetes dummy as a dichotomous variable equal to 1 if total glucose is ≥100 mg/dL and <126 mg/dL, and 0 otherwise. Likewise, the diabetes dummy equals 1 if total glucose is ≥126 mg/dL, dyslipidaemia equals 1 if total cholesterol is ≥200 mg/dL, and the inflammation dummy equals 1 if the high sensitivity C-reactive protein exceeds 2 mg/dL.…”
mentioning
confidence: 99%